Spadkobiercy "Pana Podstolego" - rzecz o wspólnej genezie "Pana Tadeusza" i "Pana Sędziego Delutego". Przyczynek do analizy zagadnienia = Heirs of "Lord Steward" - the thing about genesis of "Sir Thaddeus" and "Sir Judge Deluty". A contribution to the case study - Grabias-Banaszewska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Both texts were written nearly at the same time. Czartoryski read the Mickiewicz's epic after he had written his "Sir Judge Deluty" ["Pan Sędzia Deluty"]. There is rather no chance that Mickiewicz knew the Prince's novel. In such circumstances we cannot assume mutual influences that affected the two writings. The only presumption that may be taken into consideration is that the issuing of "Sir Thaddeus" ["Pan Tadeusz"] could have been a reason for Czartoryski to abandon works on his own novel. Nevertheless, the most significant is the fact that the two texts were created in the same time and, furthermore, they are similar in many areas. Therefore, we may ask questions what had caused such a convergence. Was it only a coincidence or did the writers have the same inspiration?
Keywords: Mickiewicz, Adam (1798-1855); Czartoryski, Adam Jerzy (1770-1861); Krasicki, Ignacy (1735-1801); "Pan Tadeusz"; "Pan Podstoli"; "Pan Sędzia Deluty"; "Lord Steward"; "Sir Thaddeus"; "Sir Judge Deluty"